Syndrome of the Trephined: A Systematic Review. Issue 4 (1st August 2016) - Ashayeri, Kimberly; Jackson, Eric M.; Huang, Judy; Brem, Henry; Gordon, Chad R.
Abstract: BACKGROUND: Syndrome of the trephined (SoT) is a rare, important complication of a craniectomy characterized by neurological dysfunction that improves with cranioplasty. Its varied symptoms include motor, cognitive, and language deficits. Its exact characterization appears suboptimal, with differing approaches of evaluation. Accordingly, this topic is in great need of further investigation. OBJECTIVE: To accurately describe SoT and explore methods of an objective diagnosis/evaluation. METHODS: Electronic searches of PubMed, MEDLINE, Web of Knowledge, and PsycINFO databases used the key words "syndrome of the trephined" and "sinking skin flap." Non English-language and duplicate articles were eliminated. Title and abstract reviews were selected for relevance. Full-text reviews were selected for articles providing individual characteristics of SoT patients. RESULTS: This review identified that SoT most often occurs in male patients (60%) at 5.1 ± 10.8 months after craniectomy for neurotrauma (38%). The average reported craniectomy is 88.3 ± 34.4 cm 2 and usually exists with a "sunken skin flap" (93%). Symptoms most commonly include motor, cognitive, and language deficits (57%, 41%, 28%, respectively), with improvement after cranioplasty within 3.8 ± 3.9 days. Functional independence with activities of daily living is achieved by 54.9% of patients after 2.9 ± 3.4 months of rehabilitation. However, evaluation of SoT is inconsistent, with only 53% of reports documenting objective studies. DISCUSSION: SoT is a variable phenomenon associated with a prolonged time to cranioplasty. Due to current weaknesses in objectivity, we hypothesize that SoT is often underdiagnosed and recommend a multifaceted approach for consistent evaluation. CONCLUSION: SoT is a serious complication that lacks exact characterization and deserves future investigation. Improved understanding and recognition have important implications for early intervention and patient outcomes.